The Concept of Wasathiyah in Islamic Shari'ah According to Yusuf Al-Qaradhawi - Arif, Khairan Muhammad (Ikatan Da'i Indonesia, 2025)
Wasathiyah Islam, or Islamic moderation, is the fruit of Imam Yusuf Al-Qaradhawi's study since 1969 on the Qur'an, As-sunnah and the essence of Islamic sharia, then became a modern school of Islamic thought that is believed to be able to present a more friendly, tolerant, peaceful and rahmatan lil alamin Islam. Therefore, the purpose of this research is to study and introduce moderate Islamic thought (wasathiy) in syari’ah by explaining its concepts, principles, signs, and characteristics according to Imam Yusuf Al-Qaradhawi. The research method uses a qualitative approach with a descriptive method of analyzing the thoughts of the characters. The main source of research is library research, most of which are the works of Imam Yusuf Al-Qardhawi related to Islamic wasathiyah. The results of the study can be summarized in 3 things, first; Islamic wasathiyah according to Al-Qaradhawi is a fair and balanced understanding and attitude between the world and the hereafter as well as material and spiritual attitudes that are not extreme right and extreme left. Second; The main principles of wasathiyah are justice, excellence, consistency, security, strength and unity. Third; In order for the understanding of the Shari'ah to be wasathiy or moderate, it must be understood according to the following signs; Understanding the nash (text) of shari'a in the context of maqashid, cause and context, understanding tsawabit and mutaghayirat (constant and flexible), being able to distinguish between goals, means and methods and being able to understand and distinguish between the teachings of faith, worship and muamalah, so as to produce fatwas or ijtihad that are in accordance with the spirit of shari'ah itself.